(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, information about the life and work of Yakubi Charkhi, as well as his place in the teachings of Sufism, is presented by mystics and scientists in different periods, and it is to justify his place in the history of philosophy that he is one of the roots of the Third Renaissance in New Uzbekistan.